The Effect of Pay-It-Forward During Disasters on Social Networks: A Network Approach - Tanimoto, Riku; Kotani, Hitomu (Journal of disaster research, 2025)
Some disaster survivors who had previously received support through volunteering participated in volunteer activities for people affected by subsequent disasters. This chain of support, known as “pay-it-forward,” is expected to expand social networks and bring about small-world property (i.e., networks with high clustering and short path length between people). Previous research has focused on the effects of pay-it-forward on individuals (i.e., the psychological perspective), but has insufficiently determined its effects on the whole society or social networks (i.e., the sociological perspective). This study investigates the dynamic effects of pay-it-forward on network properties. We proposed a network formation model considering pay-it-forward during disasters and conducted numerical simulations. The results showed that pay-it-forward led to small-world property and higher social welfare in the long term, because it eliminated the disparity in ties between people (in particular, it reduced the number of people with fewer ties), which accelerated network formation during non-disaster periods. This result was more pronounced in societies with a larger disparity in ties. From a sociological perspective, our findings imply the significance of pay-it-forward volunteering and volunteer organizations that promote such activities.